2011
DOI: 10.1002/prca.201100044
|View full text |Cite
|
Sign up to set email alerts
|

Setting proteins free: Progresses and achievements in proteomics of formalin‐fixed, paraffin‐embedded tissues

Abstract: Formalin fixation, followed by paraffin embedding, is long established as the standard procedure for the stabilization and preservation of tissue architecture, essential for enabling microscopic examination and long-term storage of samples. During the years, this has led to the generation of a worldwide repository of patient tissues with associated complete clinical records. As such, this represents a golden mine for all those attempting to identify proteomic signatures of disease, aimed to the understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 100 publications
2
49
0
Order By: Relevance
“…Archival tissue repositories are indeed a valuable resource for protein biomarker discovery and validation, since they hold a considerable number and variety of tissue specimens, including those from patients with rare malignancies, and provide retrospective information concerning diagnosis, survival, and response to therapy [2,3]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Archival tissue repositories are indeed a valuable resource for protein biomarker discovery and validation, since they hold a considerable number and variety of tissue specimens, including those from patients with rare malignancies, and provide retrospective information concerning diagnosis, survival, and response to therapy [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…In order to exploit this enormous potential, in the last years researchers have been aiming at evaluating the suitability of a wide array of techniques for FFPE tissue proteome analysis, including gel-based approaches (2DE-MS, DIGE-MS, GeLC-MS/MS [3-7]), shotgun LC-MS/MS (both label-based and label-free [8-13]), as well as targeted MS [14] and imaging MS [15]. With respect to shotgun LC-MS/MS, direct tissue trypsinization (DT) and protein extraction followed by in solution digestion (ISD) are the most commonly used strategies; more recently, an efficient alternative for processing FFPE protein extracts through the filter-aided sample preparation (FASP) workflow has been introduced [3,8,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…eral studies have shown that although the individual peptides retrieved and identified from fresh-frozen and FFPE tissues may differ, the biological information obtained from both types of material in terms of number of proteins identified, cellular location and molecular function is very similar (5)(6)(7)(8)(9)(10). A number of proteomics studies were reported, which used untargeted MS on FFPE tissues to compare diseased and healthy samples in the search for potential novel biomarkers (10).…”
mentioning
confidence: 99%
“…Proteome-level mining of this treasure trove of biomarkers was long hampered by the inaccessibility of the proteins due to extensive formalininduced covalent cross-linking. In a recent review, Tanca et al described various strategies devised for the extraction of fulllength proteins or peptides from fixed tissues, and the impact of tissue processing variables [91]. In addition, the feasibility of the analysis of the phosphoproteome and N-glycoproteome from FFPE material has also been recently shown [92].…”
Section: Label-free Discovery In Formalin-fixed Paraffin-embedded CLImentioning
confidence: 98%